Gambaran Pelaksanaan Social Distancing dan Protokol Kesehatan dimasa Pandemi Covid-19 pada Mahasiswa - Supriyadi Supriyadi; Vita Maryah Ardiyani; Novita Dewi (Wiraraja Medika : Jurnal Kesehatan, 2021)
Corona Virus Disease 2019 (COVID-19) is a respiratory disease that is becoming a worldwide epidemic during this time. Cheap and easy preventive measures to help reduce the transmission and spread of COVID-19, are including; social distancing, wearing mask, washing hands, and physical distancing. The research aim was to identify the implementation of social distancing and health protocols during the pandemic of COVID-19 among the student. The descriptive design was used to the 222 students which were selected by a simple random sampling technique. The independent variables are including social and physical distancing, wearing proper masks, and washing hands regularly. Online-based questionnaires of social distancing implementation and health protocol handed over to the participant. Data were analyzed using a sort of descriptive set. The results showed most of the participants practice the social distancing and physical distancing (64.9%), wearing proper masks (95%), and washing their hands regularly (58.1%). Further observation to the implementation of social distancing and health protocols of COVID-19 incident in the Indonesian education environment is demanding to avoid highly positive confirmed case among the university students.